The different function of single phosphorylation sites of Drosophila melanogaster lamin Dm and lamin C. - Magdalena Zaremba-Czogalla (Public Library of Science (PLoS), 2012)
Lamins' functions are regulated by phosphorylation at specific sites but our understanding of the role of such modifications is practically limited to the function of cdc 2 (cdk1) kinase sites in depolymerization of the nuclear lamina during mitosis. In our study we used Drosophila lamin Dm (B-type) to examine the function of particular phosphorylation sites using pseudophosphorylated mutants mimicking single phosphorylation at experimentally confirmed in vivo phosphosites (S(25)E, S(45)E, T(435)E, S(595)E). We also analyzed lamin C (A-type) and its mutant S(37)E representing the N-terminal cdc2 (mitotic) site as well as lamin Dm R(64)H mutant as a control, non-polymerizing lamin. In the polymerization assay we could observe different effects of N-terminal cdc2 site pseudophosphorylation on A- and B-type lamins: lamin Dm S(45)E mutant was insoluble, in contrast to lamin C S(37)E. Lamin Dm T(435)E (C-terminal cdc2 site) and R(64)H were soluble in vitro. We also confirmed that none of the single phosphorylation site modifications affected the chromatin binding of lamin Dm, in contrast to the lamin C N-terminal cdc2 site. In vivo, all lamin Dm mutants were incorporated efficiently into the nuclear lamina in transfected Drosophila S2 and HeLa cells, although significant amounts of S(45)E and T(435)E were also located in cytoplasm. When farnesylation incompetent mutants were expressed in HeLa cells, lamin Dm T(435)E was cytoplasmic and showed higher mobility in FRAP assay.